The impact of teachers’ active involvement level at MGMP of English and their perception pedagogical competence as English teacher - Saharir Saharir (Institut Agama Islam Negeri Palopo, 2023)
the impact of teachers’ active involvement level at mgmp of english and their perception pedagogical competence as english teacher English Teacher in Maros Regency, Thesis. English Department Faculty of Postgraduate Makassar Muhammadiyah University. This research aimed to know the correlation teachers’ active at MGMP and Perception pedagogic competence as English Teacher in Maros Regency. This research used a quantitative method with correlation approach. The data source of this research was primary data from ofa questionnaire and the subject of this research was 60 English teachers in Maros Regency.. Based on the data analysis, it can be concluded that teachers’ activeness involvement level at MGMP simultaneously has high correlation and their pedagogic competence. It can be described further, as the following: First from the data analysis, it is known that the significance value of Teachers’ activeness involvement at MGMP. So it can be concluded that teachers’ activeness involvement at MGMP is active to follow the MGMP activities. Second from the data analysis, it is known that the significance value of Teachers’ perception pedagogic competence. The explanation that teachers’ perception pedagogic competence of MGMP is very good. Third from the data analysis, it is known that the significance value of Teachers’ activeness involvement at MGMP (X) and teachers’ perception pedagogic competence (Y) is equal 0.01 < 0.05. This means that there is influence X (activeness involvement at MGMP) and Y (teachers’ perception pedagogic competence) have significant correlation.The result of the research showed that the teacher activeness in MGMP had positive effects, active teachers’ perception pedagogic competence also had positive effect, and the correlation teachers activeness and their perception pedagogic competence showed a significant positive relationship value of 0.01 is smaller than 0.05